Bioatividade de extratos de anonáceas e piperáceas sobre Tuta absoluta (Meyrick) (Lepdoptera: Gelechiidae) em tomateiro - Brito, Elaine Ferrari de [UNESP] (2014)
The tomato leafminer, Tuta absoluta (Meyrick), attacks the tomato crop severely, compromising the plant at all development stages. Even though the chemical control is extensively used on the management of these insect populations, less aggressive methods such as the use of plants with insecticidal activity have been investigated. This study aimed to evaluate the bioactivity of ethanolic extracts of different species and structures of the genus Annona and Piper, as well as characterize the class of compounds of the most active extracts of Annona spp. against T. absoluta. First, a screening was performed with the ethanolic extracts of the studied species. The A. muricata and Piper amalago var. medium (Jacq.) Yunck extracts showed higher activity against T. absoluta larvae and were selected and then it was determined the lethal concentrations. The effects of sub lethal doses of the extracts on the T.absoluta biology were studied, as well as the oviposition preference on the sprayed plants in choice and no-choice tests. The sub lethal effects of the extracts were not very pronounced. The extracts mainly promoted an elongation on the insect life cycle. Regarding the effect of the extracts on adults, only the P. amalago var. medium extract was classified as deterrent to oviposition. In addition, the translaminar and ovicidal effect of the extracts were also evaluated. . It was observed deleterious effect of the extracts the P. amalago var. medium on T. absoluta eggs. Regarding the translaminar effect of the extracts, it was observed that the A. muricata extracts are able to penetrate the foliar mesophyll and reach the larvae. Afterwards, the A. ...